Ion-ion collision-induced evaporative cooling of atomic and molecular ions by autoresonance in an electrostatic ion beam trap. Issue 12 (January 2020) - Heber, O; Gangwar, R K; Saha, K; Rappaport, M L; Zajfman, D
Synopsis: A new method for cooling beams of any ion is introduced. The method is autoresonance acceleration of ions inside an Electrostatic Ion Beam Trap. Intrabunch collisions of trapped (molecular) ions transfer energy from the "cold" part of the population of the ion distribution to the "hot" part, which, in turn, evaporates from the bunch. As a result, bunches of ions were cooled from about 45 K to well below 1 K.